Techniques And Strategies For Hindu Survival In Menjing Village - Made Wirahadi Kusuma (Institut Hindu Dharma Negeri Denpasar, 2019)
The role of education today is highly essential in the process of social transformation, particularly in relation to respect for pluralistic religious entities. Education as an effort to humanize humans as the aim of religious education which has been specified in Article 2 of Government Regulation No. 55/2007. It is a representative effort in forming better human qualities. Religious education is a pattern of learning dimensions that represent not only education in the formal, informal, or non-formal sense. The religious dimension that guides the community into multicultural life is built on equal right and life. The identical treatment of various differences, both religion and social status of a person is an absolute service that must be provided to everyone, so there is no one-sided discrimination against likes or dislikes, or majority or minority. Disclosure of the dominance of the majority and minority systems in Menjing has become a phenomenon examined in this study which is a struggle for the ideological dimension of the religious system between Hinduism and Islam in Menjing Village.